Study of The Implementation of the Regional Art Lovers Community Program at SMP Negeri 1 Pupuan Tabanan - Dewi, Ni Putu Rahayu Mas Ruscita; Karja, I Wayan; Mawan, I Gede (Journal of Aesthetics, Creativity and Art Management, 2025)
The background of this research stems from the importance of arts education as a foundation for developing children's emotional and social intelligence amid the challenges of globalization. Arts education not only serves as a vehicle for artistic expression but also as an effective medium for instilling values such as character, cooperation, empathy, and love for local and national culture. In the context of formal education, art is an important instrument for building children's adaptive, creative, and cultured personalities. This study aims to examine in depth the implementation of the Regional Art Lovers Community Program (Kopi Sianida) at SMP Negeri 1 Pupuan Tabanan and analyze its impact on students emotional and social development. The study employs a descriptive qualitative approach using observation, in-depth interviews, and documentation techniques. Analysis is conducted comprehensively to identify patterns of the program's impact on students, including emotional, social, and cultural preservation aspects. The research findings indicate that the Kopi Sianida program significantly enhances students artistic skills, communication, cooperation, discipline, and emotional management. Art activities based on local wisdom, such as dance, music, and dharma gita, not only strengthen cultural identity but also shape the character of the younger generation to be virtuous and resilient in facing the dynamics of the times. This program serves as a relevant and applicable model for art education that can be implemented in other schools.